Deep, low mass ratio overcontact binary systems. v. the lowest mass ratio binary V857 herculis - S. B. Qian (2018)
Charge-coupled device (CCD) photometric light curves in the B, V, and R bands of the complete eclipsing binary star V857 Her are presented. It is shown that the light curves of the W UMa-type binary are symmetric and of A type according to Binnendijk's classification. Our four epochs of light minimum along with others compiled from the literature were used to revise the period and study the period change. Weak evidence indicates that the orbital period of V857 Her may show a continuous increase at a rate of dP/dt = +2.90 × 10 -7 days yr-1. The photometric parameters of the system were determined with the 2003 version of the Wilson-Devinney code. It is shown that V857 Her is a deep overcontact binary system with f = 83.8% ± 5.1%. The derived mass ratio of q = 0.06532 ± 0.0002 suggests that it has the lowest mass ratio among overcontact binary systems. As the orbital period increases, the decrease of the mass ratio will cause it to evolve into a single rapidly rotating star when it meets the more familiar criterion that the orbital angular momentum be less than 3 times the total spin angular momentum. To understand the evolutionary state of the system, long-term photometric monitoring and spectroscopic observations will be required. © 2005. The American Astronomical Society. All rights reserved.